Bacterial vaginosis as a risk factor for lower urinary tract infection in women: case report - Konstantin P. Tevlin; Beniamin V. Khanaliev; Ekaterina V. Tevlina (IP Berlin A.V., 2022)
Conservative therapy of acute (exacerbation of chronic) cystitis in women in combination with bacterial vaginosis is a task that often causes difficulties for a practicing doctor. Escherichia coli is still the main causative agent of urinary tract infection due to the presence of virulence factors that not only affect the affinity of the pathogen to the urothelium, but also hinder the development of an immune response. At the same time, bacterial vaginosis is a factor that often accompanies and supports inflammation of the lower urinary tract in women. Simultaneous occurrence of the above conditions is a frequent clinical situation. A differential approach is needed to prescribe antimicrobials to patients with urinary tract infection and bacterial vaginosis, as well as the use of safe natural medicines (biologically active additives) in their complex therapy.